PMO-201 Bowel preparation: Moviprep® vs Klean-prep®, real life experience in unselected patients. (28th May 2012) - Disney, B R; Johnson, B; Anderson, M
Abstract : Introduction: The numbers of colonoscopies being performed has increased since the introduction of the Bowel Cancer Screening Programme. Bowel preparation is essential for a successful colonoscopy. However, bowel preparation is a major deterrent for patients undergoing screening colonoscopy. Having a bowel preparation that is more acceptable to patients may improve acceptance of bowel preparations, promote compliance and increase the likelihood of a successful procedure. The aim of this study was to assess patient tolerability of a newer bowel preparation, Moviprep ®, to the current preparation used, Klean-prep ® . Methods: Patients received either Moviprep ® or Klean-prep ® prior to colonoscopy. Each patient was asked to complete a questionnaire assessing various side effects and tolerability. Results: In total 50 patients received Moviprep ® of which 42 (84%) completed the questionnaire. Eighty-eight patients who received Klean-prep ® completed the questionnaire. The patients who received Moviprep ® suffered from fewer side effects such as, bloating (p=0.002), abdominal pain (p=0.02) and anal irritation (p=0.04). No significant differences were seen in the incidence of nausea, vomiting or abdominal cramps between the two preparations. Patients found the taste of Moviprep ® more acceptable and as a result were more likely to take all of the preparation as compared with Klean-prep ® (p=0.002). No difference was observed in the quality of bowel preparation or caecal visualisation/intubated rates (p=0.93). Conclusion: Moviprep® was tolerated much better when compared to Klean-prep® in terms of side effects and the willingness to take the preparation again. Having a preparation that is well tolerated may help with patient compliance and improve colonoscopic examination. Competing interests: None Declared.